POWER SHIFT AND SOCIO-POLITICAL CHANGES ON BANJARMASIN IN 19TH-20TH CENTURY - Wisnu Subroto (Universitas Negeri Malang, 2018)
The arrival of Dutch at Banjarmasin has become the historical pillar which signifies the changes in the life of people in many aspects. In an economic aspect, it introduced money economy. From a political aspect, it created centered administration and managed government system. This system management was refuted by the nobles because it did not suit local people system which had been long established and passed down from generation to generation. Despite this objection, the colonial government insisted on performing the management of government system in order to achieve its political goal.After the conquest of Banjarmasin in 1860, the power of colonial government got stronger. As a result, the government performed the implementation of policies and consolidation in the effort to manage administration. The Dutch Colonial government kept insisting on the idea of the administration management to ensure monitoring and centralized governance. The government’s policy had greatly influenced the mind set and perspective of the society about the importance of administration. The implementation of this administration system on the city government has resulted in changes which are greatly contrast with the prevailing culture. The status of people was no longer determined by its family background, but their position in government determined the level of social status. DOI: http://dx.doi.org/10.17977/um020v12i22017p120